2017
DOI: 10.1007/164_2017_23
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Therapy for the Treatment of Heart Failure Caused by Ischemic or Non-ischemic Cardiomyopathy: Immunosuppression and Its Implications

Abstract: HF patients with signs and symptoms of worsening heart failure (HF), despite optimal medical therapy, have a poor prognosis. The pathways contributing to HF are multiple, probably accounting, in part, for current treatment approaches not being more effective. Stem cells, particularly mesenchymal stem cells (MSCs), have a broad range of activities, making them particularly interesting candidates for a new HF therapeutic. This review presents an overview of the studies examining the efficacy of stem cell studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Two recent large meta‐analyses highlighted the paucity of high quality clinical trials assessing the evidence of MSC therapy in ICM and DCM 22, 23. Similarly, to date, there has not been a comparison between MSC therapy in patients with ICM and DCM.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent large meta‐analyses highlighted the paucity of high quality clinical trials assessing the evidence of MSC therapy in ICM and DCM 22, 23. Similarly, to date, there has not been a comparison between MSC therapy in patients with ICM and DCM.…”
Section: Introductionmentioning
confidence: 99%
“…1 This conclusion has not changed with time. 2,3 Similar conclusions are applicable to clinical trials of AMI. Although smaller trials found stem cells improve myocardial outcomes, pivotal trials have not definitively improved their prospectively identified primary end points.…”
mentioning
confidence: 59%
“…They concluded “ … to date, no cell therapy has been conclusively shown to be effective in patients with HF.” 1 This conclusion has not changed with time 2, 3. Similar conclusions are applicable to clinical trials of AMI.…”
mentioning
confidence: 70%
“…Lymphedema, characterized by tissue swelling, lipid deposition, and fibrosis due to excess accumulation of interstitial fluid and inadequate lymphatic drainage, affects 0.13%-2% of the global population[ 5 ] and remains a chronic, debilitating and incurable disease. Stem cell-based regenerative medicine has shown great promise for refractory diseases, such as inflammatory bowel diseases[ 33 ], heart failure[ 34 ], osteoarthritis[ 35 ], rheumatoid arthritis[ 36 ], and graft-versus-host disease[ 37 ]. With the properties of self-renewal, multipotential differentiation, paracrine, immunomodulatory, and trophic effects, and low immunogenicity alongside their practical advantages, ADSCs have become one of the most promising candidates for regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%